2023
DOI: 10.1097/md.0000000000032638
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum amylase levels and CD4 cell counts in newly diagnosed people living with HIV: A case-control study

Abstract: Serum amylase is a direct reflection of pancreatic injury. Several clinical studies have indicated that antiretroviral therapy may be the main cause of increased serum amylase in people living with human immunodeficiency virus (PLWH). However, other probable causes including direct human immunodeficiency virus infection, opportunistic infections and neoplasms, alcohol abuse, and use of illicit drugs, which can also affect pancreatic amylase levels were not considered in these studies. In our study, we collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Nadembega et al also stated that serum amylase levels are higher in immunocompromised patients than in those with a TCD4+ lymphocyte count above 200/mm 3 [16]. Other authors also correlated serum amylase levels with TCD4+ lymphocyte count [14,17]. Levels of viral load and CD4 lymphocyte count provide information on a patient's immune status.…”
Section: Discussionmentioning
confidence: 99%
“…Nadembega et al also stated that serum amylase levels are higher in immunocompromised patients than in those with a TCD4+ lymphocyte count above 200/mm 3 [16]. Other authors also correlated serum amylase levels with TCD4+ lymphocyte count [14,17]. Levels of viral load and CD4 lymphocyte count provide information on a patient's immune status.…”
Section: Discussionmentioning
confidence: 99%
“…Chaula et al [ 8 ] confirmed that the PCA findings showed there was no sustained medication interruption after examining the effect of azithromycin on the illustration of plasma-soluble biomarkers in adults and children who had chronic lung disease. Jin et al [ 9 ] employed logistic regression and PCA to determine whether the HIV-antibody repertoire can be used to predict the viral reservoir, and the PCA results showed that there was a correlation between the DNA of HIV patients and western blot kits; in addition, the variables were associated with the prevalence, according to the clustered indicators.…”
Section: Introductionmentioning
confidence: 99%